2020
DOI: 10.1016/j.nicl.2020.102421
|View full text |Cite
|
Sign up to set email alerts
|

Cortical gray matter progression in idiopathic REM sleep behavior disorder and its relation to cognitive decline

Abstract: Highlights Cortical degeneration over time in IRBD patients is larger than in normal aging. IRBD patients have progressive parieto-occipital and orbitofrontal thinning. Visuospatial decline in IRBD is associated with degeneration in parietal regions. Increasing motor signs in IRBD are related to frontal and parietal degeneration. Cortical thinning in posterior regions is associated with late-onset IRBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Decreased brain activity in the occipital lobe has also been reported to be associated with the delayed memory impairment [ 41 ]. A previous study has found that patients with idiopathic RBD showed decreased GMV in the occipital and parietal lobe, which were correlated with the visuospatial loss [ 42 ]. These results were similar to our study that the PD-RBD group showed reduced GMV and FC in the posterior regions than did those with PD-nRBD and significant correlation with the cognitive and motor impairment, indicating that the PD-RBD may correspond to more serious neurodegeneration and exhibit predictive value regarding the progression of motor symptoms and cognitive function, especially the visuospatial–executive function and delayed memory [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased brain activity in the occipital lobe has also been reported to be associated with the delayed memory impairment [ 41 ]. A previous study has found that patients with idiopathic RBD showed decreased GMV in the occipital and parietal lobe, which were correlated with the visuospatial loss [ 42 ]. These results were similar to our study that the PD-RBD group showed reduced GMV and FC in the posterior regions than did those with PD-nRBD and significant correlation with the cognitive and motor impairment, indicating that the PD-RBD may correspond to more serious neurodegeneration and exhibit predictive value regarding the progression of motor symptoms and cognitive function, especially the visuospatial–executive function and delayed memory [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated RBD is associated with brain volume and cortical thickness atrophy. [6][7][8][56][57][58][59][60][61] Patients also present with high rates of positivity to pathologic alpha-synuclein in tissue biopsies. [62][63][64][65] However, a mechanistic understanding of how alpha-synuclein pathology may relate to the patterns of brain atrophy in iRBD remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For cortical gray matter, structural MRI can reveal cortical volume reductions of orbitofrontal cortex [43,49], dorsolateral frontal cortex [43,49], lingual gyrus [49], cingulate cortex [43,49], fusiform gyrus [46,49], and lateral occipital cortex [46,50] in iRBD patients compared with healthy controls. Atrophy of the parietal cortex, especially of the postcentral gyri and superior parietal cortex, is also seen in iRBD [46,50,51]. A longitudinal study, including a relatively small number of iRBD patients with evidence of phenoconversion to alpha-synucleinopathy [50] showed that iRBD patients who phenoconverted had widespread thinning in the left superior frontal, right precentral, and right lateral occipital gyri compared with nonconverters at the baseline MRI with a hazard ratio of 0.784 (sensitivity of 95% and specificity of 100%), suggesting potential use as prognostic biomarkers.…”
Section: Structural Mri Diffusion Tensor Imaging Functional Mri and N...mentioning
confidence: 99%